Legal Mechanisms To Combat Terrorist Financing In Syrian Legislation - زودة , حلا; حماد, مسعود (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Within this research, our study focused on the legal mechanisms for combating terrorist financing, as stipulated by the Syrian Anti-Terrorism Law No. 19 of 2012, and Legislative Decree No. 33 of 2005 and its amendments related to money laundering and combating terrorism. The main idea of ​​the research revolves around our question about the efficacy of these mechanisms that stipulated by the Syrian legislator in the face of terrorism financing crimes, especially since it is considered one of the new crimes that the Syrian legislator has dealt within the anti-terrorism plan, as a result of the increasing risks and damages resulting from it in our current time, and accordingly we talked about the preventive mechanisms followed in this regard in its administrative and judicial aspects, as We also talked about the remedial mechanisms represented by the criminal penalty that includes penalties or measures against those who commit a terrorist financing crime.